PERAN KOMUNIKASI GURU DENGAN SISWA DALAM PEMBENTUKAN SIKAP SPIRITUAL SISWA DI SMP ISLAM MUQORROBIN SINGOSARI - Amalia Fitri Febrianti; Rosichin Mansur; Atika Zuhrotus Sufiyana (VICRATINA, 2022)
In the role of how teacher communication to students at SMP Islam Muqorrobin Singosari with the aim of forming students' spiritual attitudes runs very effectively and the response from students is very good, although there are some obstacles from some students who are a little difficult to follow the process of forming this spiritual attitude. The focus of this research is on planning teacher-student communication, what models are used in communicating with students, and of course the results of implementing teacher-student communication in the formation of students' spiritual attitudes. To achieve the focus of this research objective, the researcher uses a qualitative research method with the type of case study research with data obtained through observation, interviews, and documentation, then after the researcher finds the data needed, the researcher analyzes the data by collecting data, reducing data, and presenting the data. and draw conclusions. Then the researchers found the results of the planning research including lesson plans, then the models used were the Stimulus Response/SR communication model, Aristotle's communication model, and Tubbs' communication model. The results on the implementation of the formation of spiritual attitudes through communication methods include the assessment of students' spiritual attitudes and teacher assessments.